Inovasi Macrame Menjadi Produk Kreatif dalam Praktik Kewirausahaan dengan Nama Brand CHARMEE - Erwin Putra Rasul Dafana; Ni Made Arsita Kusumadewi; Ivonia Auxiliadora Freitas Marcal; Muhammad Yasin (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
The trend of handmade accessories, particularly macrame holders, has experienced significant growth alongside increasing public interest in products that emphasize both aesthetic value and multifunctionality. This study aims to provide an in-depth analysis of the marketing strategies implemented for CHARMEE, the Macrame Multifunction Holder, highlighting the integration of artistic elements, innovative design, and practical utility within handicrafts. Employing a qualitative descriptive method, primary data were collected through surveys of 35 respondents aged 20–35 years. The findings reveal that the use of high-quality materials, designs that are responsive to market trends, and the strategic utilization of social media and digital platforms for promotion are the main factors driving the product’s appeal and competitiveness. These results affirm that handmade products, when combined with creative and innovative marketing strategies, possess substantial potential to develop as high-value economic ventures in the era of creative entrepreneurship. The implications of this study underscore the importance of continuous innovation and adaptability to market dynamics in maintaining business relevance and sustainability.